Expression of nutrient transporters in placentas affected by gestational diabetes: role of leptin - Guadix, Pilar; Corrales, Isabel; Vilariño-García, Teresa; Rodríguez-Chacón, Carmen; Sánchez-Jiménez, Flora; Jiménez-Cortegana, Carlos; Dueñas, José L.; Sánchez-Margalet, Víctor; Pérez-Pérez, Antonio (Frontiers in Endocrinology, 2023)
Gestational diabetes mellitus (GDM) is the most frequent pathophysiological state of pregnancy, which in many cases produces fetus with macrosomia, requiring an increased nutrient transport in the placenta. Recent studies by our group have demonstrated that leptin is a key hormone in placental physiology, and its expression is increased in placenta from GDM. However, the effect of leptin on placental nutrient transport, such as glucose, amino acids, and lipids is not fully understood. That is why, we aimed to review the literature regarding the leptin effect involved in placental nutrient transport, as well as the activated leptin signaling pathways involved in the expression of placental transporters, which may contribute to the increase in placental nutrient transport in human pregnancies complicated with GDM. Leptin appears to be a relevant key hormone that regulates placental transport, and this regulation is altered in pathophysiological conditions such as gestational diabetes. Adaptations in the placental capacity to transport glucose, amino acids, and lipids may underlie both under-or overgrowth of the fetus when maternal nutrient and hormone levels are altered due to changes in maternal nutrition or metabolic disease. Implementing new strategies to modulate these placental transports may improve maternal health and prove effective in normalizing fetal growth in cases of intrauterine growth restriction and fetal overgrowth. However, further studies are needed to confirm this hypothesis.